Impact of time to chest closure on early and late survival in adults with delayed sternal closure. (7th February 2023) - Crestanello, Juan A; Greason, Kevin; Elsisy, Mohamed; Lahr, Brian; Bagameri, Gabor; Daly, Richard; Stulak, John; Dearani, Joseph; Schaff, Hartzell
Abstract: OBJECTIVES: Delayed sternal closure (DSC) after cardiac surgery is a temporizing measure to address coagulopathy or haemodynamic instability after cardiac surgery. We sought to study: (i) indications and temporal trends for DSC, (ii) factors associated with time to chest closure and (iii) its impact on short-term and long-term outcomes. METHODS: From January 2007 to December 2017, 494 patients (median age 67 years, 66% males) required DSC after cardiac surgery. Medical records were reviewed for indications, risk factors, time to DSC and outcomes. Multivariable Cox regression via landmark analysis of 486 5-day survivors was used to investigate the impact of time to chest closure on early and late survival. RESULTS: Coagulopathy and haemodynamic instability were the most common indications. Median time to chest closure was 2 days. Pre-/intraoperative extracorporeal membranous oxygenation, severe right ventricular dysfunction and diabetes mellitus were associated with longer time to chest closure. Longer time to closure was associated with increased risk of operative complications and operative mortality, but did not have a statistically significant association with late mortality. Increasing age, pulmonary hypertension and a greater number of prior sternotomies were also found to be associated with overall mortality. CONCLUSIONS: While longer time to chest closure was associated with increased rates of operative complications and operative mortality, it did not reveal a statistically significant association with long-term survival. Abstract : Delayed sternal closure (DSC) is a temporizing measure used to address coagulopathy or haemodynamic instability after cardiac surgery [1–5].